Cardiorespiratory sleep studies at home: experience in research and clinical cohorts. Issue 5 (19th November 2018) - Kingshott, Ruth N; Gahleitner, Florian; Elphick, Heather E; Gringras, Paul; Farquhar, Michael; Pickering, Ruth M; Martin, Jane; Reynolds, Janine; Joyce, Anna; Gavlak, Johanna C; Evans, Hazel J; Hill, Catherine M
Abstract : Objective: To evaluate the success rates of home cardiorespiratory polygraphy in children under investigation for sleep-disordered breathing and parent perspectives on equipment use at home. Design: Prospective observational study. Setting: Sheffield, Evelina London and Southampton Children's Hospitals. Patients: Data are reported for 194 research participants with Down syndrome, aged 0.5–5.9 years across the three centres and 61 clinical patients aged 0.4–19.5 years from one centre, all of whom had home cardiorespiratory polygraphy including respiratory movements, nasal pressure flow, pulse oximetry, body position and motion. Main outcome measures: Percentage of home cardiorespiratory studies successfully acquiring ≥4 hours of artefact-free data at the first attempt. Parental report of ease of use of equipment and preparedness to repeat home diagnostics in the future. Results: 143/194 (74%; 95% CI 67% to 79%) of research participants and 50/61 (82%; 95% CI 71% to 90%) of clinical patients had successful home cardiorespiratory polygraphy at the first attempt. Some children required multiple attempts to achieve a successful study. Overall, this equated to 1.3 studies per research participant and 1.2 studies per clinical child. The median artefact-free sleep time for successful research studies was 515 min (range 261–673) and for clinical studies 442 min (range 291–583). 84% of research and 87% of clinical parents expressed willingness to repeat home cardiorespiratory polygraphy in the future. 67% of research parents found the equipment 'easy or okay' to use, while 64% of clinical parents reported it as 'easy' or 'very easy'. Conclusions: Home cardiorespiratory polygraphy offers an acceptable approach to the assessment of sleep-disordered breathing in children.